Adolescent and Parent Perceptions about Participation in Biomedical Sexual Health Trials. Issue 3 (18th May 2020) - Landers, Sara E.; Francis, Jenny K. R.; Morris, Marilyn C.; Mauro, Christine; Rosenthal, Susan L.
ABSTRACT: Given the burden of HIV and other sexually transmitted infections among adolescents who are legal minors, it is critical that they be included in biomedical sexual health trials to ensure that new prevention and treatment interventions are safe, effective, and acceptable for their use. However, adolescents are often not well represented in clinical trials. We provide an overview of the available evidence regarding adolescent and parent willingness for adolescents to participate in biomedical sexual health trials, parental involvement in the permission‐consent process, management of differences and discord among adolescents and parents, and parental involvement throughout the study period. We also outline recommendations for current practice and areas for future research.